2011
DOI: 10.1073/pnas.1100872108
|View full text |Cite
|
Sign up to set email alerts
|

KCNE1 enhances phosphatidylinositol 4,5-bisphosphate (PIP 2 ) sensitivity of I Ks to modulate channel activity

Abstract: Phosphatidylinositol 4,5-bisphosphate (PIP 2 ) is necessary for the function of various ion channels. The potassium channel, I Ks , is important for cardiac repolarization and requires PIP 2 to activate. Here we show that the auxiliary subunit of I Ks , KCNE1, increases PIP 2 sensitivity 100-fold over channels formed by the pore-forming KCNQ1 subunits alone, which effectively amplifies current because native PIP 2 levels in the membrane are insufficient to activate all KCNQ1 channels. A juxtamembranous site in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(148 citation statements)
references
References 53 publications
10
137
1
Order By: Relevance
“…If dormant states reflect an early closed state in the activation pathway, two slow transitions are needed to explain this behavior, one to account for the seconds needed for the channel to activate ordinarily and another, even slower, transition to account for the sometimes long dormant periods that can last many minutes. Alternatively, the long dormant state we observe may not be part of the linear activation pathway but instead may be an alternative gating mode of the channel, similar to that seen for sodium (35) and calcium (36) channels, and may be influenced by turnover of molecules that modulate I Ks activity, such as Phosphatidylinositol 4,5-bisphosphate (PIP2), ATP, PKA, or calmodulin (37)(38)(39)(40). It is likely that channels can be recruited from dormant to active states in the face of sympathetic activation when I Ks function becomes most prominent, but this possibility remains to be proven (38,41).…”
Section: Resultsmentioning
confidence: 99%
“…If dormant states reflect an early closed state in the activation pathway, two slow transitions are needed to explain this behavior, one to account for the seconds needed for the channel to activate ordinarily and another, even slower, transition to account for the sometimes long dormant periods that can last many minutes. Alternatively, the long dormant state we observe may not be part of the linear activation pathway but instead may be an alternative gating mode of the channel, similar to that seen for sodium (35) and calcium (36) channels, and may be influenced by turnover of molecules that modulate I Ks activity, such as Phosphatidylinositol 4,5-bisphosphate (PIP2), ATP, PKA, or calmodulin (37)(38)(39)(40). It is likely that channels can be recruited from dormant to active states in the face of sympathetic activation when I Ks function becomes most prominent, but this possibility remains to be proven (38,41).…”
Section: Resultsmentioning
confidence: 99%
“…However, our data demonstrate that PIP 2 is required to link the activation of the VSD to the PD; therefore, if fewer than four PIP 2 binding sites are occupied, the PD will not be functionally coupled to all four VSDs. Indeed, the activation of Kv7.1 is far from saturated by the endogenous level of PIP 2 available in the oocyte membrane (32) such that most of the channel population may have only one PIP 2 bound and one VSD coupled. In addition, a recent study suggested that the voltage-dependent activation of Kv7.1 can be explained by an allosteric model where activation of only one VSD can open the channel (27).…”
Section: Discussionmentioning
confidence: 99%
“…The steady-state fluorescence data are fit with a single (or double) Boltzmann and normalized between the minimum and maximum fluorescence for each experiment. Thermodynamic mutant cycle analysis was conducted as described previously (48). The amount of free energy required to shift the S4 from the resting to the activated state was calculated as ΔG 0 C→A = -zFV 1/2 , where z and V 1/2 were measured from the F(V) and F is Faraday's number.…”
Section: Methodsmentioning
confidence: 99%